2021
DOI: 10.1186/s12936-021-03634-0
|View full text |Cite
|
Sign up to set email alerts
|

Seeking research questions from implementers: considerations for leveraging ground actors research needs in the fight against malaria in West Africa

Abstract: Background To strengthen the fight against malaria, it is imperative to identify weaknesses and possible solutions in order to improve programmes implementation. This study reports experiences gained from collaboration between decision-makers and researchers from a World Bank project (Malaria and Neglected Tropical Diseases in the Sahel, SM/NTD). The objectives of this paper were to identify bottlenecks in malaria programme implementation as well as related research questions they bring up. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The process used for this research prioritization effort aimed to build upon other recent malaria research prioritization efforts. The desk review revealed a few country- and regional-level malaria research agendas that included some similarly themed operational research questions [ 29 – 32 ]. However, most of these agendas were set between 2015 and 2017 and were thus somewhat outdated.…”
Section: Discussionmentioning
confidence: 99%
“…The process used for this research prioritization effort aimed to build upon other recent malaria research prioritization efforts. The desk review revealed a few country- and regional-level malaria research agendas that included some similarly themed operational research questions [ 29 – 32 ]. However, most of these agendas were set between 2015 and 2017 and were thus somewhat outdated.…”
Section: Discussionmentioning
confidence: 99%